Pengaruh Distribusi Agregat Dari Produk Campuran Hrs Base Terhadap Parameter Marshall - Tiung, Yustina Fatima; Trisnoyuwono, Diarto; Alokabel, Koilal (JUTEKS : Jurnal Teknik Sipil, 2024)
Road service quality can be determined by qualitative assessment (safety and comfort). The quality of the surface layer is one of the parameters. The HRS Base hot mix asphalt surface course, for example, is often a product failure. One of the reasons is the mismatch between the design results and the production of the mixture, for example, the gradation of mixed aggregates whose composition may deviate due to weaknesses in the production process at AMP. The first variation (10% more coarse aggregate) did not meet the specifications because there were several parameters that did not meet the requirements, namely VIM, VFB, MQ, and residual marshall stability, the second and third variations (10% less coarse aggregate and 10% more fine aggregate) the parameter values of VIM, VFB, MQ and residual marshall stability did not meet the specification requirements and only the parameter values of stability and VMA met the specifications. In the fourth variation (10% less coarse aggregate and 10% more fine aggregate), some of them met the specifications but there were two marshall parameter values that did not meet the specifications, namely the MQ value and the residual marshall stability, while in the control variable all the marshall parameter values met the specification requirements